Limitace metanogeneze v degradovaných rašeliništích po revitalizaci jejich vodního režimu - Pocová, Michaela (Jihočeská univerzita, 2017)
The aim of this thesis was to determine limitation of methanogenesis in restored peatlands and effect of different substrates on potential methane production in restored bog and spruce swamp forest soil. Study sites were located in Šumava National Park in the Czech Republic.
Limitation of methanogenesis in degraded peatlands after revitalization their water regime
Keywords: rašeliniště; metanogeneze; substrát; revitalizace; metanogeni; methanogenezis; peatlands; substrat; revitalization; methanogens